1998
DOI: 10.1177/107906329801000308
|View full text |Cite
|
Sign up to set email alerts
|

The Case Against Licensing Health Professionals

Abstract: In the interest of full disclosure, I am a licensed psychologist. Yet I oppose licensing. I remain licensed because I wish to continue to practice my profession. My opposition to both general and specialty licensure is the subject of this paper.To understand my position requires knowing that state governments, under the umbrella of their police powers, grant licensing to a profession to protect the welfare of the public. The licensing act reserves either a title (i.e., psychologist) or a practice (i.e., psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…This is an inevitable result. (p. 372) Twenty-five years later, Gross (1998) agreed with Roger's prediction, saying that licensing had resulted in psychologists achieving acceptability but at the cost of "a decreased tolerance for diversity" and "support for values which work in the marketplace and which replace psychology's traditional research and service values" (p. 258). I see this as evidence of societal regression.…”
Section: Drawbacks To Licensing Of Psychotherapistsmentioning
confidence: 82%
See 3 more Smart Citations
“…This is an inevitable result. (p. 372) Twenty-five years later, Gross (1998) agreed with Roger's prediction, saying that licensing had resulted in psychologists achieving acceptability but at the cost of "a decreased tolerance for diversity" and "support for values which work in the marketplace and which replace psychology's traditional research and service values" (p. 258). I see this as evidence of societal regression.…”
Section: Drawbacks To Licensing Of Psychotherapistsmentioning
confidence: 82%
“…8). And in an article titled "The Case Against Licensing Health Professionals," Gross (1998) wrote, "My review of the empirical research shows no substantial relationship between licensing and quality of service measures. Evaluations of the work of licensing agencies also show they do not protect the public" (p. 257).…”
Section: The Concept Of Emotional Process In Societymentioning
confidence: 99%
See 2 more Smart Citations
“…Hall (1995) found that community treatment was more eective than institution treatment; thus, where treatment is received may be important. The training, credentials, and experience of the treatment providers, currently a subject of some debate (e.g., Gross, 1998;Jensen & Jewell-Jensen, 1998), may in¯uence treatment eectiveness. It may also be important to consider the gender of the treatment providers (e.g., Langevin et al, 1979).…”
Section: How Are the Data Analyzed?mentioning
confidence: 99%